FGF13 promotes metastasis of triple‐negative breast cancer. Issue 1 (24th February 2020) - Johnstone, Cameron N.; Pattison, Andrew D.; Harrison, Paul F.; Powell, David R.; Lock, Peter; Ernst, Matthias; Anderson, Robin L.; Beilharz, Traude H.
Abstract : Triple‐negative breast cancer (TNBC) represents 10–20% of all human ductal adenocarcinomas and has a poor prognosis relative to other subtypes, due to the high propensity to develop distant metastases. Hence, new molecular targets for therapeutic intervention are needed for TNBC. We recently conducted a rigorous phenotypic and genomic characterization of four isogenic populations of MDA‐MB‐231 human triple‐negative breast cancer cells that possess a range of intrinsic spontaneous metastatic capacities in vivo, ranging from nonmetastatic (MDA‐MB‐231_ATCC) to highly metastatic to lung, liver, spleen and spine (MDA‐MB‐231_HM). Gene expression profiling of primary tumours by RNA‐Seq identified the fibroblast growth factor homologous factor, FGF13, as highly upregulated in aggressively metastatic MDA‐MB‐231_HM tumours. Clinically, higher FGF13 mRNA expression was associated with significantly worse relapse free survival in both luminal A and basal‐like human breast cancers but was not associated with other clinical variables and was not upregulated in primary tumours relative to normal mammary gland. Stable FGF13 depletion restricted in vitro colony forming ability in MDA‐MB‐231_HM TNBC cells but not in oestrogen receptor (ER)‐positive MCF‐7 or MDA‐MB‐361 cells. However, despite augmenting MDA‐MB‐231_HM cell migration and invasion in vitro, FGF13 suppression almost completely blocked the spontaneous metastasis of MDA‐MB‐231_HM orthotopic xenografts to both lung and liver while having negligible impact on primary tumour growth. Together, these data indicate that FGF13 may represent a therapeutic target for blocking metastatic outgrowth of certain TNBCs. Further evaluation of the roles of individual FGF13 protein isoforms in progression of the different subtypes of breast cancer is warranted. Abstract : What's new? Triple‐negative breast cancer (TNBC) has a high degree of molecular diversity, with multiple subtypes and varying metastatic behavior. To better understand TNBC heterogeneity, the authors of this study performed RNA expression analysis on four isogenic MDA‐MB‐231 human TNBC tumour models characterized by distinct metastatic capacities. The three metastatic variants upregulation of the fibroblast growth factor FGF13. Elevated FGF13 expression was associated with poor survival in patients with basal‐like breast cancer. In mice, FGF13 knockdown in highly metastatic MDA‐MB‐231 cells reduced spontaneous metastasis to liver and lung without affecting primary xenograft growth, suggesting that FGF13 is a promising antimetastatic target.